Development of Interactive Flipbooks on Positive and Negative Integer Counting Operation Materials for Elementary School Students - Rachman, Kufita; Nur Romadhon, Nofian; Rossa Nurjayanti, Alvindi (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
Technology must be utilized to develop interactive learning to build students' motivation to learn and deepen their understanding of subject-related concepts. This study focuses on the development of interactive page-turning instruction using positive and negative integer arithmetic as teaching materials to make it feasible and practical. The population of this study consists of sixth-grade students of SD Negeri Bawuran. The research methodology was based on the ADDIE model of Research and Development (R&D), which includes analysis, design, development, implementation, and evaluation stages. Data collection was conducted through interviews and questionnaires. The results of the interview data were analyzed descriptively, and the questionnaire data were analyzed statistically. The development of the interactive flipbook received a mean score of 89.75% for the material validation, including very feasible, and a mean score of 94% for the media validation, including very feasible. The results of students' responses on the usefulness of the interactive flipbook received a mean score of 85.7%, including very useful, thus the use of the interactive flipbook in mathematics learning is good.